Будівельно-інжинірингові фірми – нові учасники ринку будівельних інвестицій - Орищенко, В. В. (Ways to Improve Construction Efficiency, 2014)
It is in-process offered bases of realization of important structural constituent of process of adaptation of operating of home building production conditions to the eurorequirements. Transformation of mutual relations of leading performer is in-process certain leading pre-condition of such adaptation with a customer - from traditionally inferior to project-engineering.